Separation Anxiety among Kindergarten Children and its Association with Parental Socialization - Samar Jreisat (Health Psychology Research, 2023)
The present study aimed at investigating the association between separation anxiety and parental socialization styles among a sample of kindergarten children in Amman city, Jordan. The study adopted the descriptive cross-sectional design. A sample of 300 kindergarten children were enrolled in this study. The researcher used a modified version of the separation anxiety scale in addition to the parental socialization styles scale. Data were analyzed using the Statistical Package of Social Sciences (SPSS) (v. 27, IBM Corp.). The results of the study showed that 8% (n=24) of the enrolled participants had a high level of separation anxiety, normality parenting style was adopted by 38.7% (n=116). The results showed that there was significant statistical association between separation anxiety and cruelty parenting style (r=0.465, p=0.003), overprotection parenting style (r=0.301, p=0.000), negligence parenting style (p=0.641, p=0.04), and normality (r=0.09, p=0.000). The results showed that separation anxiety is significantly associated with parental socialization styles in general (r=0.326, p=0.007).